2013
DOI: 10.1111/vru.12085
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Findings Related to Prognosis in Canine Transitional Cell Carcinoma

Abstract: In human bladder cancer patients, ultrasonography is extensively used not only to identify tumor masses but also to evaluate tumor size, shape, echogenicity, location, and degree of tumor invasion into the bladder wall. The information revealed by ultrasonography delineates the tumor's biological features and facilitates prediction of prognosis. However, in veterinary medicine the feasibility of using ultrasonography for these purposes has not been fully investigated. In this retrospective study, we reviewed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
0
21
0
2
Order By: Relevance
“…A study reported ultrasonographic findings such as wall involvement, heterogeneous mass and trigone location could be reliable prognostic indicators in canine TCC [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study reported ultrasonographic findings such as wall involvement, heterogeneous mass and trigone location could be reliable prognostic indicators in canine TCC [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary difference between these species was the location of the mass. Location of the mass has been previously associated with shorter survival times in dogs; a trigonal mass had shorter survival times . The trigonal masses have an increased probability of urinary obstruction by physically occluding the tapered transition from the bladder neck to the urethra.…”
Section: Discussionmentioning
confidence: 95%
“…These therapies are aimed at reducing the tumor volume to palliate clinical signs, thus improving quality of life. Surgical intervention is often difficult because the disease is frequently in a trigonal location and may have a multifocal distribution . Mapping of the bladder to characterize the location of the transitional cell carcinoma tumor is poignant in the clinical evaluation and staging for disease to determine if surgery is an option .…”
Section: Introductionmentioning
confidence: 99%